Identifikasi Pasien Berpengaruh terhadap Keselamatan Pasien (Journal of Hospital Management, 2019)
The high issue of incident report in 2018 in X Hospital was particulary related with the patient’s identification and effective communication which focuses on reporting laboratory critical value can inhibit the follow-up treatment and patient safety. This research aims to provide empirical evidenve of the effect of patient’s identification and effective communication of patient safety through the quality of hospital services. The research method used quantitative analytical method with causality research design. Analysis unit is inpatient unit in X hospital. Data analysis being used is multinomial logistic analysis and multiple regression. The results of this research showed that patient’s identification and effective communication also the quality of hospital services were significantly affected patient safety. The findings of this research is patient’s identification had positive affected and significant on patient safety and quality of hospital services. Effective communicatioan which focuses on reporting laboratory critical value not affected on patient safety and quality of hospital services. Quality of hospital services not mediate patient safety cause patient’s identification and effective communication influence directly on patient safety.Keywords: safety, identification, effective communication, quality of services